How do you solve y = 3x - 4 and 2x - y = 1?

2 Answers

The solution is (x,y)=(3,5)

Explanation:

Hence you have two linear equations we have that

y=3x-4 and y=2x-1

since the first parts are equal so the second are

3x-4=2x-1=>x=3 and y=2*3-1=5

Sep 25, 2015

x = 3
y = 5

Explanation:

y= 3x - 4 rArr 1st equation
2x - y = 1 rArr 2nd equation

Since y is already the subject of the first equation, all you need to do is substitute y = 3x - 4 into the 2nd equation!

So,

2x - (3x - 4) = 1

Expand the brackets.

2x - 3x + 4 = 1

Which gets you:

-x + 4 = 1

Move the 4 over so x becomes your subject.

-x = -4 + 1
-x = -3

Switch them over so your x is positive!

3 = x

To find y, just substitute x = 3 into either the 1st of 2nd equation.

So,

y = 3(3) - 4
y= 9 - 4
y = 5

To check:
Substitute the values of x and y back into the equation. You will get the same answer.